Tradisi Ma’baca Baca sebagai Refleksi Keimanan Masyarakat Suku Bugis - Mubarak, Azhar (Fahima, 2024)
Cultural diversity in Indonesia makes Islam assimilate, to avoid conflicts that occur in society. One form of assimilation, especially in the Bugis community, is that there is a tradition that is practiced by the community known as ma’baca baca. This study aims to determine the relevance of the tradition of ma’baca baca to the faith of the Bugis community. The research method used was descriptive qualitative, data collection through interviews, and data validation through member checks. There were five respondents used in the study. The results found that there is a dilemma in carrying out the ma’baca baca tradition, alongside that the ma’baca baca tradition also functions as a reinforcement for society in increasing piety, social values, and also as a reflection of life found in the ma'read-read tradition.